KONTRIBUSI SEKTOR KEHUTANAN PADA PEMBANGUNAN DAERAH KABUPATEN BLORA - Suparmoko M. (Economic Journal of Emerging Markets, 2008)
This study is aimed to establish a more reliable measurement called Environmentally Friendly GRDP case of the forestry sector of Blora. The study is adopting the descriptive analytical approach by computing the depletion value of forest natural resources and the degradation value of the environment related to the forest cutting using primary and secondary data. Results of the study indicate that depreciation of forest resources were quite high (approximately 30% of the forest GRDP). So if depreciation of natural resources and environment is neglected and not accounted in the report of GRDP, in turns the sustainability of forest and the economy is in danger. It is therefore to be recommended that Green GRDP must be adopted and computed in order the Governement of each region of Indonesia are able to prepare a better plan and management of the natural resources for long term sustainbale development.Keywords: environmentally friendly GRDP, depletion, degradation, unit rent, benefit transfer